Antioxidant activity of hydro-alcoholic extracts of 4 citrus species flower - Nabavi, Seyed Fazel; Nabavi, Seyed Mohammad; Ebrahimzadeh, Mohammad Ali (Progress in Nutrition, 2016)
Objectives: During past two decades, much attention has been paid to antioxidant activity of different edible parts of medicinal plants. Present study aimed to evaluate antioxidant activity of hydro-alcoholic extract of flowers of Citrus aurantium, Citrus nobilis, Citrus limon and Citrus sinensis. Methods: Biological activities of hydro-alcoholic extract of Citrus aurantium, Citrus nobilis, Citrus limon and Citrus sinensis flowers were investigated employing different in vivo and in vitro assay systems including DPPH, nitric oxide and H2O2 scavenging models, Fe2+ chelating, reducing power model, linoleic acid system test, as well as H2O2-induced hemolysis test. Results: Citrus limon extract showed best activity in DPPH and nitric oxide radicals scavenging activity and Fe2+ chelating activity than others. Citrus nobilis extract exhibited better H2O2 scavenging. Extracts exhibited good antioxidant activity in linoleic acid system test that were comparable with vitamin C (p>0.05). The extracts showed weak reducing power activity. Citrus sinensis showed better antihemolytic activity against H2O2 induced hemolysis. Conclusion: Combining data showed that hydro-alcoholic extract of flowers of 4 Citrus species possess antioxidant activity in different assay systems.